Magnesium-lithium alloy strength and plasticity synergistic improvement method based on nano precipitation strengthening and severe plastic deformation and application of magnesium-lithium alloy strength and plasticity synergistic improvement method

By performing nanoprecipitation strengthening and violent plastic deformation in Mg-9Li-3Al-1Zn alloy, the contradiction between the strength and plastic properties of Mg-Li alloy is solved, and its EMI shielding ability and comprehensive mechanical properties are significantly improved.

CN119120955APending Publication Date: 2024-12-13HARBIN ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310691682.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

When the existing Mg-Li alloys increase their strength, their plastic properties decrease, making it difficult to meet the comprehensive performance requirements of electronic device shells, and their EMI shielding capabilities are insufficient.

Method used

By performing nano-precipitation strengthening and violent plastic deformation in Mg-9Li-3Al-1Zn alloy, including vacuum electromagnetic induction smelting, homogenization treatment, solid solution-aging heat treatment and accumulation and stacking process, a small second phase with diffuse distribution is formed. Improve the strength and plasticity of the alloy.

Benefits of technology

It significantly improves the comprehensive mechanical properties of Mg-Li alloy, enhances its EMI shielding ability, and achieves a coordinated improvement of high strength and high plasticity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119120955A_ABST
    Figure CN119120955A_ABST
Patent Text Reader

Abstract

The invention relates to a magnesium-lithium alloy strength and plasticity synergistic improvement method based on nano precipitation strengthening and severe plastic deformation and application of the magnesium-lithium alloy strength and plasticity synergistic improvement method. The invention belongs to the field of magnesium-lithium alloy. According to the preparation method disclosed by the invention, through good cooperation of reasonable component design, solid solution-aging heat treatment and hot rolling deformation, good regulation and control on factors such as the number, the morphology and the type of the second phases in the double-phase Mg-Li alloy are realized, namely, the second phases which are dispersed in distribution, regular in morphology, large in number and fine are obtained. A fine and unagglomerated hard second phase is introduced into a metal matrix to improve the strength and plasticity of the alloy, meanwhile, deformation of an accumulative ply rolling process is effectively utilized, improvement on the mechanical property of the Mg-Li alloy is strengthened, dynamic precipitation of the second phase and formation of fine recrystallization are promoted through rolling, and the mechanical property of the Mg-Li alloy is improved. And subcrystal and harder MgLi2Al and softer AlLi particles are obtained through subsequent aging treatment, so that the comprehensive mechanical property of the Mg-Li alloy is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of magnesium-lithium alloys, and specifically relates to a method and application for synergistically improving the strength and plasticity of magnesium-lithium alloys based on nano-precipitation strengthening and severe plastic deformation. Background Art

[0002] Nowadays, more and more efficient, convenient and cheap electronic products appear in people's daily lives. Electronic products generate electromagnetic waves (EM) when working, and the disordered and ultra-high intensity radiation of electromagnetic waves will produce electromagnetic wave pollution. Electromagnetic wave pollution not only interferes with the normal operation of other electronic products, but also harms human health and vegetation growth. Therefore, how to shield electromagnetic interference (EMI) has received more and more attention. With the energy conservation, emission reduction and carbon neutrality concepts advocated by countries around the world, the development of a lightweight, cheap material with superior mechanical properties and excellent EMI shielding ability is currently a hot topic.

[0003] As the best green materials in the 21st century, Mg and its alloys are very promising lightweight application structural materials due to their low density and high specific strength. Mg-Li alloy is considered to be the lightest structural metal material (ρMg-Li, 1.35-1.65g / cm3), which is widely used in lightweight fields such as aerospace, medical equipment, automobiles, 3C, etc. The Li content in the alloy is a key factor affecting the microstructure and performance of this series of alloys. When the Li content is between 5.7wt% and 10.3wt%, the Mg-Li alloy exhibits a HCPα-Mg+BCCβ-Li dual-phase structure. Among them, α-Mg is a Mg solid solution formed by Li dissolving in Mg, and β-Li is a Li solid solution formed by Mg dissolving in Li. The HCPα-Mg+BCCβ-Li dual-phase structure combines the advantages of HCP (high strength) and BCC (many slip systems and good plasticity). In addition, experiments have shown that the HCPα-Mg+BCCβ-Li dual-phase structure plays a positive role in enhancing the EMI shielding ability of Mg-Li alloys. Strength, plasticity and EMI shielding performance are the three basic requirements for Mg-Li alloys as shielding materials. However, the strength of Mg-Li alloys is relatively low and is not enough to meet the requirements of electronic device housings. Methods commonly used to improve the performance of Mg-Li alloys include alloying (such as Al, Zn, RE), heat treatment (such as solid solution, aging), plastic deformation (such as rolling, extrusion), etc. However, the increase in strength is often accompanied by a decrease in plasticity. The decrease in plasticity is not conducive to the deformation processing of materials. Therefore, it is very necessary to reasonably adjust the comprehensive performance required by Mg-Li matrix EMI shielding materials. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, the present invention provides a method and application for synergistically improving the strength and plasticity of a magnesium-lithium alloy based on nano-precipitation strengthening and severe plastic deformation.

[0005] The purpose of the present invention is to achieve the following technical solutions:

[0006] One of the purposes of the present invention is to provide a method for synergistically improving the strength and plasticity of a magnesium-lithium alloy based on nano-precipitation strengthening and severe plastic deformation, the method being carried out in the following steps:

[0007] S1: Preparation of Mg-9Li-3Al-1Zn alloy by vacuum electromagnetic induction melting furnace;

[0008] S2: homogenizing the as-cast Mg-9Li-3Al-1Zn alloy at 210-230°C for 8-12h, followed by solution treatment;

[0009] S3: cutting the alloy wire after solution treatment into plates, and then performing cumulative rolling;

[0010] S4: performing aging treatment on the rolled alloy to obtain a magnesium-lithium alloy.

[0011] It is further defined that the smelting process in S1 is as follows: pure magnesium ingots, pure lithium ingots, pure aluminum ingots and pure zinc ingots are weighed according to the stoichiometric ratio of the Mg-9Li-3Al-1Zn alloy, and then smelted under argon protection.

[0012] It is further defined that the homogenization treatment in S2 is performed at 220° C. for 10 h.

[0013] It is further defined that the solution treatment temperature in S2 is 400°C, maintained for 3 h, and then water quenched to room temperature.

[0014] It is further defined that the sample is polished, sanded and preheated before S3 cumulative rolling.

[0015] It is further defined that the rolling temperature in S3 is 200°C.

[0016] It is further defined that during the S3 cumulative rolling process, the reduction in a single pass is greater than 50%, and the total deformation is 50%.

[0017] It is further defined that the aging treatment temperature in S4 is 100°C and the temperature is kept for 12 hours.

[0018] A second object of the present invention is to provide a high-strength plastic magnesium-lithium alloy obtained by the above method.

[0019] The third object of the present invention is to provide a high-strength plastic magnesium-lithium alloy obtained by the above method for use in the field of electromagnetic shielding.

[0020] Compared with the prior art, the present invention has the following significant effects:

[0021] The present invention achieves good control of the number, morphology, type and other factors of the second phase in the two-phase Mg-Li alloy through reasonable composition design, good coordination of solid solution-aging heat treatment and hot rolling deformation, that is, a dispersed distribution, regular morphology, large number and fine second phase is obtained. A fine and non-agglomerated hard second phase is introduced into the metal matrix to improve the strength and plasticity of the alloy, and at the same time, the deformation of the cumulative rolling process is effectively utilized to strengthen the improvement of the mechanical properties of the Mg-Li alloy. The dynamic precipitation of the second phase and the formation of fine recrystallization are promoted by rolling, and sub-grains, harder MgLi2Al and softer AlLi particles are obtained by subsequent aging treatment, thereby significantly improving the comprehensive mechanical properties of the Mg-Li alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Figure 1 is the microstructure of the aged Mg-9Li-3Al-1Zn alloy obtained in Example 1; (a) is the TEM image of recrystallized grains and subgrains, and the inset is the corresponding SAED image; (b) is the HRTEM image of Figure (a); (c) is the HRTEM image of the large-angle grain boundary in area 1 in Figure (b), and (d) is the HRTEM image of the small-angle grain boundary in area 2 in Figure (b);

[0023] Figure 2 Room temperature tensile stress-strain curves of Mg-9Li-3Al-1Zn alloys in different states;

[0024] Figure 3 AEM images of tensile fractures of Mg-9Li-3Al-1Zn alloy in different states: (a) - cast state, (b) - solid solution state, (c) - solid rolling state, and (d) - aged state. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0026] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0027] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0028] When equivalent, concentration or other value or parameter is represented by the range limited by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the scope is intended to include its end value and all integers and fractions within the scope. In the present application specification and claims, range limitation can be combined and / or interchanged, if these ranges are not otherwise stated, include all sub-ranges contained therein.

[0029] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.

[0030] The "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0031] Embodiment 1:

[0032] The method for synergistically improving the strength and plasticity of magnesium-lithium alloy based on nano-precipitation strengthening and severe plastic deformation of this embodiment is carried out in the following steps:

[0033] S1. Preparation of Mg-9Li-3Al-1Zn alloy:

[0034] First, pure magnesium ingot (99.9wt.%), pure lithium ingot (99.9wt.%), pure aluminum ingot (99.9wt.%), and pure zinc ingot (99.9wt.%) are weighed according to the stoichiometric ratio of Mg-9Li-3Al-1Zn alloy. In order to ensure the purity of the alloy obtained by smelting, the surfaces of magnesium ingot, aluminum ingot, and zinc ingot need to be polished clean before smelting, and the lithium ingot needs to be taken out of the kerosene before discharging. The above raw materials are placed in a graphite crucible, and the raw materials with high melting point are placed at the bottom of the crucible;

[0035] Subsequently, the vacuum degree in the furnace was evacuated to below 0.1 Pa, and then argon gas was introduced into the furnace to 0.05 MPa. The melt was melted in a vacuum induction furnace under the protection of argon atmosphere, and the melt was poured into a mold to obtain an ingot.

[0036] S2, homogenization, solution heat treatment:

[0037] First, the as-cast Mg-9Li-3Al-1Zn alloy ingot was homogenized at 220 °C for 10 h;

[0038] Subsequently, the alloy was solution treated at 400 °C for 3 h and quenched in water to room temperature. To prevent the alloy from oxidation, it was wrapped with tin foil before heat treatment, then buried in a crucible filled with MgO powder, and finally placed in a box-type resistance furnace for heat treatment.

[0039] S3, Accumulative Rolling:

[0040] First, the alloy wire after solution treatment was cut into plates (50 mm × 65 mm × 2 mm), and then the sample was polished with a wire brush, and then the traces on the surface of the sample were polished off with sandpaper, wrapped with tin foil, and placed in a box-type resistance furnace for preheating before rolling;

[0041] Then the sample was taken out and the tin foil was removed. A double-roller uniform-speed rolling mill was used for cumulative rolling at 200°C. Four layers of plates were stacked and fed into the rolling mill along the 65mm long side. The initial thickness was 8mm, and the single-pass reduction was set to 50%. The thickness after the first rolling pass was 4mm. After rolling, it was kept warm at 200°C for 10 minutes again, and then the second rolling pass was carried out. The thickness after the second rolling pass was 2mm. The thickness was kept at 4mm by stacking, and it was kept warm at 200°C for 10 minutes again, and then the third rolling was carried out. The third rolling process was repeated until the cumulative rolling was completed 5 times, and the final rolling thickness was 2mm.

[0042] S4. Aging treatment:

[0043] The rolled plate was kept at 100°C for 12 hours for aging heat treatment to obtain a high-strength plastic magnesium-lithium alloy. In order to prevent the alloy from oxidation, it was wrapped with tin foil before heat treatment, then buried in a crucible filled with MgO powder, and finally placed in a box-type resistance furnace for heat treatment.

[0044] (a) Microstructure observations were performed using optical microscopy (OM), scanning electron microscopy (SEM) equipped with energy dispersive X-ray spectroscopy (EDS), and transmission electron microscopy (TEM). Figure 1As shown in the figure, it can be seen that since all changes in the recovery process do not involve large-angle grain boundary migration, only the dissipation of point defects in the grains and the change of dislocation structure, the recrystallized grains formed in the rolled alloy still maintain their original shape. The rearrangement of dislocations forms small-angle grain boundaries and subgrains, and the migration of these small-angle grain boundaries coarsens the subgrains. Therefore, the recrystallized grains and subgrain structures in the aged alloy are both nanoscale. Through aging treatment, a uniformly distributed nano-precipitated MgLi2Al strengthening phase is obtained in the matrix. At the same time, the ultra-fine grain size is obtained by utilizing the severe plastic deformation process characteristics of cumulative rolling, and finally the synergistic improvement of the strength and plasticity of the magnesium-lithium alloy is achieved.

[0045] (ii) The room temperature tensile test of Mg-9Li-3Al-1Zn alloy in different states was carried out using a tensile tester (tensile rate of 1 mm / min). The strength and elongation of the alloy are shown in Table 1. The average value was obtained from three parallel tensile tests. The room temperature tensile stress-strain curves of Mg-9Li-3Al-1Zn alloy in different states are shown in Figure 2 As shown in the figure, it can be seen that the tensile strength and elongation of the cast Mg-9Li-3Al-1Zn alloy are 188MPa and 27.5% respectively. After solution treatment, the tensile strength of the alloy is significantly improved, and its value is 259MPa, but the elongation decreases to 19.7%. The tensile strength of the rolled alloy is further improved, and its value is 293MPa, but the elongation is seriously reduced, and its value is only 9.2%. In the subsequent aging treatment process, the elongation of the Mg-9Li-3Al-1Zn plate is effectively improved. The elongation of the aged alloy is greatly increased to 24.6%, while the tensile strength is only slightly reduced to 252MPa.

[0046] Table 1 Mechanical properties of Mg-9Li-3Al-1Zn alloy in Example 1

[0047] Sample status Tensile strength / MPa Elongation / % Cast 188 27.5 Solid solution 259 19.7 Rolling 293 9.2 Time-limited state 252 24.6

[0048] (III) Observe the microstructure of the fracture surface after room temperature tensile test. Figure 3 As shown, the fracture morphology of the cast alloy has many large and deep dimples, showing obvious ductile fracture characteristics. The fracture morphology of the cast alloy after solid solution shows a large number of small and shallow dimples, and its fracture mode is still ductile fracture. The rolled alloy shows typical brittle fracture, and its fracture morphology includes large tear ridges and obvious river flowers. Many small and deep dimples can be found in the fracture morphology of the aged alloy, indicating that the fracture mode of the alloy has changed from brittle fracture of the rolled state to ductile fracture. Large and deep dimples indicate that the elongation of the material is good, and shallow dimples indicate that the elongation is relatively poor.

[0049] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for synergistically improving the strength and plasticity of magnesium-lithium alloys based on nano-precipitation strengthening and severe plastic deformation, characterized in that: Follow these steps: S1: Preparation of Mg-9Li-3Al-1Zn alloy by vacuum electromagnetic induction melting furnace; S2: homogenizing the as-cast Mg-9Li-3Al-1Zn alloy at 210-230°C for 8-12h, followed by solution treatment; S3: cutting the alloy wire after solution treatment into plates, and then performing cumulative rolling; S4: performing aging treatment on the rolled alloy to obtain a magnesium-lithium alloy.

2. The method according to claim 1, characterized in that The smelting process in S1 is as follows: pure magnesium ingots, pure lithium ingots, pure aluminum ingots and pure zinc ingots are weighed according to the stoichiometric ratio of the Mg-9Li-3Al-1Zn alloy, and then smelted under argon protection.

3. The method according to claim 1, characterized in that: In S2, the homogenization treatment was carried out at 220°C for 10 h.

4. The method according to claim 1, characterized in that: The solution treatment temperature in S2 is 400 °C, which is maintained for 3 h and then quenched in water to room temperature.

5. The method according to claim 1, characterized in that Before S3 cumulative rolling, the samples were polished, sanded and preheated.

6. The method according to claim 1, characterized in that The rolling temperature in S3 is 200°C.

7. The method according to claim 1, characterized in that During the S3 cumulative rolling process, the single-pass reduction is greater than 50%, and the total deformation is 50%.

8. The method according to claim 1, characterized in that The aging treatment temperature in S4 is 100°C and kept at this temperature for 12 hours.

9. A high-strength plastic magnesium-lithium alloy obtained by the method according to any one of claims 1 to 8.

10. Application of the high-strength plastic magnesium-lithium alloy obtained by the method according to any one of claims 1 to 8 in the field of electromagnetic shielding.